2020
DOI: 10.1136/bmjopen-2019-034361
|View full text |Cite
|
Sign up to set email alerts
|

Association between topical beta-blockers and risks of cardiovascular and respiratory disease in patients with glaucoma: a retrospective cohort study

Abstract: ObjectiveTo determine if topical beta-blocker use is associated with increased risks of cardiovascular and respiratory diseases in patients with glaucoma.SettingA retrospective cohort analysis was conducted using the database from Taiwan’s National Health Insurance programme.ParticipantsIn total, 12 336 newly diagnosed patients with glaucoma from January 2000 to December 2010 were included. The patients with glaucoma were subdivided into two cohorts according to whether they used topical beta-blockers or combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Fibrates for dyslipidemia and inhaled corticosteroids for asthma were also reported to increase the risk of glaucoma and elevate IOP 32,33. On the contrary, recently, both a retrospective cohort study in Taiwan and a meta-analysis suggested that these side effects were overly exaggerated 34,35…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrates for dyslipidemia and inhaled corticosteroids for asthma were also reported to increase the risk of glaucoma and elevate IOP 32,33. On the contrary, recently, both a retrospective cohort study in Taiwan and a meta-analysis suggested that these side effects were overly exaggerated 34,35…”
Section: Discussionmentioning
confidence: 99%
“…32,33 On the contrary, recently, both a retrospective cohort study in Taiwan and a meta-analysis suggested that these side effects were overly exaggerated. 34,35 Nevertheless, the strong association between systemic diseases and glaucoma indicates that patients with glaucoma should be referred for regular general examinations and that internal physicians should refer patients for regular ophthalmological examinations, which will assist in clinical decision-making. Regarding the association between glaucoma and lifestyle habits, several studies have found that smokers and drinkers have a higher IOP and glaucoma prevalence than the reference group.…”
Section: Discussionmentioning
confidence: 99%